Combined Effects of Forest Conservation and Population Resettlement on the Ecological Restoration of Qilian Mountain National Park - Xi Wang; David Lopez-Carr; Liang Zhou (Land)
The combined pressures of climate change and human activities have exacerbated ecological risks in fragile and sensitive areas. Assessing the ecological restoration status of key nature reserves and developing a new conservation and development framework are fundamental for achieving ecological civilization and enhancing sustainability. As an ecological security barrier in the northwestern alpine region, Qilian Mountain National Park (QMNP), is of great significance for maintaining the sustainable ecological environment of western China. By measuring changes in ecological land use and monitoring key vegetation indicator trends in QMNP, we constructed the Regional Ecological Resilience Indicator (RERI) and proposed a new restoration and restoration framework. The results show that: (1) the ecological land restoration in QMNP was remarkable, with a total of 721.76 km2 of non-ecological land converted to ecological land, representing a 1.44% increase. Forest restoration covered 110 km2, primarily made up of previously unused land from 2000 to 2020. (2) The average NDVI value increased by 0.025. Regions showing productivity growth (NPP) accounted for 51.82% of the total area from 2000 to 2020. The four typical eco-migration zones reduced the building profile area by 47.72% between 2015 and 2019. The distribution of high Composite Vegetation Index (CFI) values overlapped with concentrated forest restoration areas, revealing two main restoration models: forest conservation and population relocation. (3) RERI calculations divided the park into three ecological zones, Priority Conservation Area (PCA), Optimization and Enhancement Area (OEA), and Concerted Development Area (CDA), leading to the proposal of an ecological restoration and development framework for QMNP, characterized by “three zones, two horizontal axes, and one vertical axis”. Our findings contribute to strengthening the ecological security barrier in northwestern China; they offer new insights for the long-term, stable improvement of the ecological environment in QMNP and in other critical protected area systems globally.